Compression performance and analytical model of hexagonal-core sandwich panels fabricated by 3D printed continuous carbon fiber-reinforced thermosetting epoxy composites. (1st August 2022) - Xin, Zhibo; Ming, Yueke; Duan, Yugang; Wang, Ben; Yang, Qiang
Abstract: Composite sandwich structures are widely used in a multitude of fields owing to their excellent properties, such as light weight and high strength. In this study, a series of hexagonal-core sandwich panels were integrally fabricated by three-dimensional (3D) printed continuous fiber reinforced thermosetting epoxy composites. The influence of the scaling effects that is, the side length and layer thickness on the compression performance of these structures was studied. The experimental results showed that the specific strengths of three different hexagonal-core sandwich panels with different side lengths of 5 mm, 10 mm and 20 mm side lengths is roughly maintained at 0.018 MPa/(kg m −3 ). In addition, doubling the wall thickness of the hexagonal core increases the compressive strength by only 38.9%. The performance characteristics of these hexagonal-core sandwich panels, which change with size, can provide a reference for designers and can be used for the preliminary prediction of the structural strength.